2018
DOI: 10.1017/s0022215117002614
|View full text |Cite
|
Sign up to set email alerts
|

Stentless mirrored L-shaped septonasal flap versus stented flapless technique for endoscopic endonasal repair of bilateral congenital choanal atresia: a prospective randomised controlled study

Abstract: The endoscopic approach utilising a flap without stenting is safe and effective, with a high success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For the purpose of preventing restenosis and subsequent reoperation, many authors advocate preserving the mucosa for use as flaps. From a 1990 report describing an initial pharyngeal mucosa flap with a star-shaped incision, variously designed shapes of mucosal flaps have been published, including the swinging door flap, mirrored L-shaped septonasal flap, nasal septal cross-over flap, and folded-over-flap [ 3 , 8 , 15 , 23 ]. However, adopting the same mucosal flap design for different atretic types is impractical because of the limitations of each technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of preventing restenosis and subsequent reoperation, many authors advocate preserving the mucosa for use as flaps. From a 1990 report describing an initial pharyngeal mucosa flap with a star-shaped incision, variously designed shapes of mucosal flaps have been published, including the swinging door flap, mirrored L-shaped septonasal flap, nasal septal cross-over flap, and folded-over-flap [ 3 , 8 , 15 , 23 ]. However, adopting the same mucosal flap design for different atretic types is impractical because of the limitations of each technique.…”
Section: Discussionmentioning
confidence: 99%
“…A vertical incision was made from top to bottom at the cartilaginous/bony junction through the septal mucosa approximately 5–10 mm anterior to the atretic plate (the inferior aspect of the middle turbinate was used as a landmark for the superior limit of dissection, that can reduce the risk if cutting near or through the posterior septal artery), following to the floor of the nasal cavity, reaching the lateral wall of the nasal cavity (hence the name “L-shaped”) [ 3 ]. The mucosal flap over the thickened vomer and the nasal face of the atretic plate was elevated carefully to achieve maximal preservation of the mucosa and harvested flap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in surgical outcomes were seen with or without the use of stents, as the rate of restenosis was 42.9% with stent and 47.4% without a stent. Tomoum et al [27] reported a comparative evaluation of the endoscopic repair of CA in 72 newborns using a mirrored L-shaped flap without stenting versus stenting without a flap. Patient follow-up revealed higher granulation tissue in patients with a stent (53.3%) than without (28.6%) and 33.33% stenosis in patients with stent and 21.40% in patients without a stent.…”
Section: Reviewmentioning
confidence: 99%
“…The operation for patients with unilateral CA might be delayed until school age. 2,3 In the literature, the disease has been evaluated in terms of etiopathogenesis, 4 surgical treatment approaches, 5,6 and accompanying diseases. 7 However, few articles have evaluated anesthesia management of patients with special features like CA.…”
mentioning
confidence: 99%